2021
DOI: 10.3390/ph14020153
|View full text |Cite
|
Sign up to set email alerts
|

Pharyngeal Pumping and Tissue-Specific Transgenic P-Glycoprotein Expression Influence Macrocyclic Lactone Susceptibility in Caenorhabditis elegans

Abstract: Macrocyclic lactones (MLs) are widely used drugs to treat and prevent parasitic nematode infections. In many nematode species including a major pathogen of foals, Parascaris univalens, resistance against MLs is widespread, but the underlying resistance mechanisms and ML penetration routes into nematodes remain unknown. Here, we examined how the P-glycoprotein efflux pumps, candidate genes for ML resistance, can modulate drug susceptibility and investigated the role of active drug ingestion for ML susceptibilit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 68 publications
0
15
0
Order By: Relevance
“…Transcriptional changes in these channels in resistant, relative to drug-susceptible, parasite strains have been demonstrated previously; for example, the glutamate-gated chloride channel subunits ( glc-3, glc-5 ), as well as p- glycoprotein ABC transporters ( pgp-1, pgp-2, pgp-9 ) ( 54 ) in the MHco18(UGA) strain. Similarly, a pgp-9 copy number variant was associated with ivermectin resistance in a genetic cross and bulk segregant experiment in the related nematode T. circumcincta ( 46 ), while transgenic overexpression of the equine parasitic nematode Parascaris univalens pgp-9 modulated ivermectin sensitivity in C. elegans ( 68 ). However, none of these genes were identified in regions of differentiation after treatment in this study, suggesting these genes are not the direct target of selection.…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptional changes in these channels in resistant, relative to drug-susceptible, parasite strains have been demonstrated previously; for example, the glutamate-gated chloride channel subunits ( glc-3, glc-5 ), as well as p- glycoprotein ABC transporters ( pgp-1, pgp-2, pgp-9 ) ( 54 ) in the MHco18(UGA) strain. Similarly, a pgp-9 copy number variant was associated with ivermectin resistance in a genetic cross and bulk segregant experiment in the related nematode T. circumcincta ( 46 ), while transgenic overexpression of the equine parasitic nematode Parascaris univalens pgp-9 modulated ivermectin sensitivity in C. elegans ( 68 ). However, none of these genes were identified in regions of differentiation after treatment in this study, suggesting these genes are not the direct target of selection.…”
Section: Discussionmentioning
confidence: 99%
“…To identify transgenic worms, a plasmid driving pharyngeal gfp expression in C. elegans was co-injected. Expression of the Cyp was under the control of the C. elegans intestine epithelium-specific gut esterase 1 promotor ( ges-1p ) [ 38 ], since IVM uptake was demonstrated to occur via active pharyngeal pumping through the gut epithelium [ 39 ] and xenobiotic metabolism is primarily assumed to take part in the gut epithelium of nematodes [ 40 ]. The WT was used as the control line since Gerhard et al [ 39 ] did not observe significant differences between WT and mock-transduced nematodes using almost identical constructs.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, except for macrocyclic lactones, in silico results suggests that the anti- A. cantonensis activity may be correlated with lipophilicity and molecular weight; these parameters may be important to facilitate the permeation of the compounds through the parasite’s surface ( Lago et al, 2019 ; Xavier et al, 2020 ) and, consequently, the interaction with their molecular target(s). Regarding the permeation of the macrocyclic lactones, a recent study using the model nematode Caenorhabditis elegans has shown that expression of P-glycoproteins in specific barrier tissues, i.e., the epidermis and the intestine can impact the susceptibility to different macrocyclic lactones ( Gerhard et al, 2021 ). The authors demonstrated that active drug ingestion increases susceptibility to ivermectin considerably and to moxidectin only moderately.…”
Section: Discussionmentioning
confidence: 99%